Rumen-derived lipopolysaccharide enhances the expression of lingual antimicrobial peptide in mammary glands of dairy cows fed a high-concentrate diet. Issue 1 (December 2016) - Jin, Di; Chang, Guangjun; Zhang, Kai; Guo, Junfei; Xu, Tianle; Shen, Xiangzhen
Abstract Background Long-term high-concentrate diet (HCD) feeding can cause subacute ruminal acidosis in cows and subsequently trigger systemic inflammatory and immune responses. Therefore, we conducted the present study in which twelve lactating cows installed with ruminal fistula were randomly assigned to the HCD group (forage:concentrate = 4:6, n  = 6) or the low-concentrate diet (LCD) group (forage:concentrate = 6:4, n  = 6) and were fed for 20 weeks. Ruminal fluid, plasma and mammary gland tissue samples were collected at week 20 for analysing lipopolysaccharide (LPS), pro-inflammatory cytokines, and immune relevant gene expression. The aim of this study was to investigate the effect of rumen-derived LPS on lingual antimicrobial peptide (LAP) synthesis and immune responses in mammary glands of lactating cows fed a HCD. Results Compared with the LCD group, the ruminal pH was lower in the HCD group, while LPS concentrations in the rumen, lacteal artery and vein were higher. The expression of LAP, BNBD5, IL-1β, IL-6, IL-8, and TNF–α was enhanced in the HCD group. LAP protein expression was higher in the HCD group than that in the LCD group. The expression of nuclear factor kappa B (NF-кB) did not change, but was activated, as the amounts of phosphorylated NF-kB and phosphorylated inhibitory kBα increased in the HCD group compared with that in the LCD group. Conclusions After long-term HCD feeding, rumen-derived LPS translocated to the blood stream, triggered inflammatory and immune responses and enhanced LAP synthesis via the NF-kB signalling pathway in mammary glands of lactating cows.